Nanoencapsulation of flavonoid bioactives using the nanoprecipitation technique - Review - Sacramento, Marina da Silva; Tavares, Maria Inês Bruno (Seven Editora, 2024)
Various food processing industries have been focusing on creating new foods from functional foods due to the growing demand for healthier habits. The class of flavonoids has significant therapeutic potential, with antioxidant and anti-inflammatory attributes attributed to the bioactives present in functional foods. Nanoencapsulation carried out through the nanoprecipitation technique is an effective method to encapsulate these bioactives in polymeric matrices, allowing the generation of a material with a longer shelf life, extracted from these types of foods. This enables the production of nutraceuticals, with a focus on generating dietary supplementation/improvement for human health. Thus, the objective of this seminar was to present studies on bioactives with antioxidant properties, derived from the flavonoid group, nanoencapsulated through the nanoprecipitation technique. This technique demonstrated efficacy in the generation, bioavailability, and shelf life enhancement of nutraceuticals. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-180